Развитие рынка и политики энергосервисных компаний - United Nations Economic Commission for Europe (United Nations, 2016)
It examines the current status of ESCO development in twelve countries participating in the project. For the purposes of the report all participating countries are divided into three groups: member states of the European Union (EU), South-Eastern European countries and countries of Eastern Europe and Central Asia (the latter represented by Kazakhstan). The development of the ESCO market in these countries is not at the same level. The proposed grouping helps examine the current situation with ESCOs in the countries based on their geographical situation and neighborhood as well as the membership in and/or relationship with the EU. Information presented in this report is based on the results of desk research, findings of the Regional Analysis of Policy Reforms to Promote EE and RE Investments (undertaken earlier in the framework of the FEEI project), information provided by the National Coordinators (NCs) and National Participation Institutions (NPIs) in the framework of the project, consultations with experts in the ESCO market area and other available information.